Yemen's solar revolution: Developments, challenges, opportunities - Dawud Ansari; Claudia Kemfert; Hashem al-Kuhlani (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
Yemen has been involved in a civil war with foreign military intervention since 2014. Throughout the conflict, the majority of the population have been cut off from the public electricity grid. However, as alternatives have been unavailable, the country has turned to decentralised solar energy, giving rise to an unprecedented deployment of solar (home) systems. This report uses own calculations, new household surveys, and extensive literature research to document Yemen's solar revolution. While the report identifies central drivers for the diffusion of solar energy, it also discovers critical barriers: Since 2017, growth in the solar sector has been stagnating, since bottlenecks in the sector hamper a further diffusion. The article concludes with a set of recommendations for both international and local actors, and it shows how targeted funding and projects can set the course for sustainable development, energy access, and climate change mitigation simultaneously.
Additional information: Report with policy recommendations. based on results from research projects financed by the Federal Ministry of Education and Research ("FoReSee", 01LA1811B) and the Energy Access and Development Program ("The future of Yemen's energy sector").
Keywords: 330